An investigation into the correlation between Spiritual Intelligence and communication skillsamong nursing students - Shahnaz salawati ghasemi; Sholeh Shami; Nazila Olyaie; Taban Nematifard; Mona Nemati; Maryam Khorshidi (Kurdistan University of Medical Sciences, 2017)
Background & Aim: The key to playing role in the nursing profession is the proper communication and is, in fact, the basic part of nurses' careers in looking after the patients. Recognizing the factors related to communication skills of nursing students, including spiritual intelligence, can be used to increase the quality of care. The purpose of this study was to investigate the correlation between spiritual intelligence and communication skills of nursing students in Kurdistan University of Medical Sciences. Materials & Methods: In this descriptive-correlational study, 286 nursing students were selected by stratified sampling method. Data were collected by King’s Spiritual Intelligence Questionnaire and Barton’s Communication Skills Questionnaire. Data analysis was done by descriptive and inferential statistics using SPSS 21 software. Results: The mean age of the students was 21.37±2.39 years. Most of the students were male (55%) and studying in the fourth year of the university (30%) (Seventh semester (17.1%)). The mean (standard deviation) of spiritual intelligence was 59.71 (12.04) and communication skills was 51.83 (10.10). Based on Pearson correlation coefficient, the correlation between communication skills with spiritual intelligence and its areas was positive (0.414) and was statistically significant (p<0.05). Conclusion: There was a positive and significant correlation between spiritual intelligence and communication skills. Considering this issue in students, along with physical, mental and social dimensions, can increase the communication skills and increase the quality of nursing care in the future.